RETRACTED: An Efficient Ultrasound-Assisted Synthesis of Cu/Zn Hybrid MOF Nanostructures With High Microbial Strain Performance - Abdieva, Gulnora Abdullaevna; Patra, Indrajit; Al-Qargholi, Basim; Shahryari, Taher; Chauhan, Narendra Pal Singh; Moghaddam-manesh, Mohammadreza (Frontiers in Bioengineering and Biotechnology, 2022)
Metal organic frameworks (MOFs) are a promising choice for antibacterial and antifungal activity due to their composition, unique architecture, and larger surface area. Herein, the ultrasonic method was used to synthesize Cu/Zn-MOF material as effective hybrid nanostructures with ideal properties. SEM images were used to investigate the product's morphology and particle size distribution. The XRD pattern revealed that the Cu/Zn-hybrid MOF nanostructures had a smaller crystalline size distribution than pure Cu and Zn-MOF samples. Furthermore, the BET technique determined that the hybrid MOF nanostructures had a high specific surface area. TG analysis revealed that the hybrid MOF structures were more thermally stable than pure samples. The final product with remarkable properties was used as a new option in the field of antibacterial studies. Antibacterial activity was assessed using MIC and MBC against Gram-negative and Gram-positive strains, as well as antifungal activity using MIC and MFC. The antimicrobial properties of the synthesized Cu/Zn- hybrid MOF nanostructures revealed that they were more effective than commercial drugs in some cases. This study's protocol could be a new strategy for introducing new hybrid nanostructures with specific applications.